An econometric evaluation of daylight saving time in Mexico. (15th November 2019) - Flores, Daniel; Luna, Edgar M.
Abstract: Since the First World War, several countries use daylight saving time (DST). However, evaluations of DST started until the 1970s. Given the difficulties of finding data around the moment in which DST started, econometric studies usually evaluate changes to DST. We have aggregate data on residential electricity consumption in Mexico from 1982 to 2016. DST started in 1996. Therefore, our data covers a large period both before and after DST started. Moreover, DST is in effect only during part of the year (from April to October). Hence, we can evaluate the effects of DST with a differences-in-differences (DID) econometric approach. As far as we know, there is only another DID econometric study using similar data. Such study takes advantage of a short period in which DST was adopted and then repealed in Australia. Since our data covers a larger period, we can control for trends in consumption, calculate savings in different DST months, and run robustness tests. Our estimates indicate that savings due to DST account for 0.5% of total electricity consumption. Nevertheless, the effect of DST is not homogeneous along the period. This is important because estimates based on DST extensions may not reflect the effects of DST itself. Highlights: We evaluate the impact of daylight saving time on electricity consumption in Mexico. We use a differences-in-differences econometric approach to evaluate DST. Our data covers a large period both before and after DST started in Mexico. Residential savings due to DST represent 0.5% of total electricity consumption. Savings are larger towards the end of the DST period.